Reflective Functioning on the Parent Development Interview: validity and reliability in relation to socio-demographic factors. Issue 3 (3rd May 2020) - Sleed, Michelle; Slade, Arietta; Fonagy, Peter
ABSTRACT: The Reflective Functioning coding of the Parent Development Interview (PDI-RF) is a widely used method for assessing a caregivers' capacity for mentalization. However, little is known about its psychometric properties. The aim of this study was to examine the distributions and discriminant and criterion validity of the PDI-RF scale in relation to a number of demographic and socioeconomic factors. Mothers of infants and toddlers ( N = 323) from low, medium, and high-risk samples were interviewed with the PDI and transcripts were coded for RF. Demographic and socio-economic data were recorded. The PDI-RF scale showed high inter-rater reliability, internal consistency, and criterion validity. Modest associations with some sociodemographic variables and PDI-RF were found, but together these only accounted for a small amount of variance in the measure, suggesting adequate discriminant validity. Overall, the scale had good psychometric properties, although some caveats for its use were identified.